State space modelling of semiconductors with ideal switches, resistors, constant voltage and current sources - Demir, Y; Köksal, M (Springer-Verlag, 2004)
New concepts are introduced to model strongly nonlinear resistive and reactive nonlinear power components. The models introduced are composed of linear time-invariant passive RLC elements, dependent sources, ideal switches, as well as constant voltage and current sources. In addition to the conventional component behavioural equations, these models are made complete by defining the so-called control inequalities between the terminal variables. Completely different components may lead to the same circuit model, but having different control inequalities, they perform their own characteristics. The method of component modelling is very convenient for the state-space analysis technique, the unification of which results in the complete state--space description of the whole system. Even if there are discontinuities in the state variables, the analysis is possible without dealing with the theory of distributions, the problems of large and small time constants, and any numerical integration.
Keywords: piecewise linearization; power semiconductors; switching equations; state equations; control inequalities